HUBUNGAN WAKTU TUNGGU OBAT DENGAN KEPUASAN PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT IBU DAN ANAK SANTA ANNA 2024: RELATIONSHIP BETWEEN DRUG WAITING TIME AND OUTPATIENT SATISFACTION IN HOSPITAL PHARMACY INSTALLATIONS MOTHER AND CHILD SANTA ANNA 2024 - Nopiyansyah; Wahyuni, Novita Tri; Hijrah; Handayani, Kartika; Wahidah, Lilik Koernia (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
The waiting time for non-concocted drug services is the period from the patient submitting the prescription to receiving the finished drug with a minimum standar of<30 minutes, while the waiting time for concocted drugs is the period from the patient giving the prescription to the patient receiving the concoction with a period of <60 minutes. This study aims to see how long the waiting time for medication is with patient satisfaction. This study uses an observational research design with a cross sectional approach conducted at the Santa Anna Mother and Child Hospital Bandar Lampung. The sampling technique uses the Accidental sampling method with a total of 100 respondents. Data analysis in this study uses the chi-square testing technique. The results of this study were obtained by respondents of female gender (62%), male (38%), age 17-25 years (27%), 26-35 years (29%), 36-45 years (23%), 46-55 years (15%), 55-65 years (6%), diagnosis of ISPA (34%), dyspepsia (17%), February (17%), hypertension (5%), Antenatal Care (27%). The waiting time for medication is not according to the standard (19%) and the time is not according to the standard (81%), patients feel dissatisfied (20%), feel satisfied (80%). The results of the chi-square test of drug waiting time with patient satisfaction were obtained score (p= 0.000), meaning that Ho was rejected and Ha was accepted, this indicates that there is a relationship between drug waiting time and patient satisfaction. Keywords: Drug waiting time, patient satisfaction, hospital